N-acetylcysteine use among patients undergoing cardiac surgery: A systematic review and meta-analysis of randomized trials - Pereira, Jose Eduardo G. [UNESP]; El Dib, Regina [UNESP]; Braz, Leandro Gobbo [UNESP]; Escudero, Janaina [UNESP]; Hayes, Jason; Johnston, Bradley C. (Public Library Science, 2019)
Background Cardiac surgeries are complex procedures aiming to re-establish coronary flow and correct valvular defects. Oxidative stress, caused by inflammation and ischemia-reperfusion injury, is associated with these procedures, increasing the risk of adverse outcomes. N-acetylcysteine (NAC) acts as an antioxidant by replenishing the glutathione stores, and emerging evidence suggests that NAC may reduce the risk of adverse perioperative outcomes. We conducted a systematic review and meta-analysis to investigate the addition of NAC to a standard of care among adult patients undergoing cardiac surgery. Methods We searched four databases (PubMed, EMBASE, CENTRAL, LILACS) from inception to October 2018 and the grey literaure for randomized controlled trials (RCTs) investigating the effect of NAC on pre-defined outcomes including mortality, acute renal insufficiency (ARI), acute cardiac insufficiency (ACI), hospital length of stay (HLoS), intensive care unit length of stay (ICULoS), arrhythmia and acute myocardial infarction (AMI). Reviewers independently screened potentially eligible articles, extracted data and assessed the risk of bias among eligible articles. We used the GRADE approach to rate the overall certainty of evidence for each outcome. Results Twenty-nine RCTs including 2,486 participants proved eligible. Low to moderate certainty evidence demonstrated that the addition of NAC resulted in a non-statistically significant reduction in mortality (Risk Ratio (RR) 0.71; 95% Confidence Interval (CI) 0.40 to 1.25), ARI (RR 0.92; 95% CI 0.79 to 1.09), ACI (RR 0.77; 95% CI 0.44 to 1.38), HLoS (Mean Difference (MD) 0.21; 95% CI -0.64 to 0.23), ICULoS (MD -0.04; 95% CI -0.29 to 0.20), arrhythmia (RR 0.79; 95% CI 0.52 to 1.20), and AMI (RR 0.84; 95% CI 0.48 to 1.48). Limitations Among eligible trials, we observed heterogeneity in the population and interventions including patients with and without kidney dysfunction and interventions that differed in route of administration, dosage, and duration of treatment. This observed heterogeneity was not explained by our subgroup analyses. Conclusions The addition of NAC during cardiac surgery did not result in a statistically significant reduction in clinical outcomes. A large randomized placebo-controlled multi-centre trial is needed to determine whether NAC reduces mortality.